Lack of Evidence of Chikungunya Virus Infection among Blood Donors during the Chikungunya Outbreak in Lazio Region, Italy, 2017 - Giulietta Venturi; Massimo Fabiani; Antonello Amendola; Giulia Marsili; Eleonora Benedetti; Cristiano Fiorentini; Claudia Fortuna; Simonetta Pupella; Patrizio Pezzotti; Stefania Vaglio; Giulio Pisani; Vincenzo De Angelis; et al. (Viruses, 2022)
Background: The latest European Chikungunya virus (CHIKV) outbreak occurred in Italy in 2017, in the municipalities of Anzio and Rome (Lazio Region), with a secondary outbreak in the Calabrian Region. Most CHIKV infections are symptomatic but about 15% of people who acquire the infection may be asymptomatic. A retrospective study was conducted with the aim of assessing the prevalence of recent/ongoing CHIKV infections on the blood donor population in the Lazio Region, during the 2017 outbreak (including in the period before it was detected). Methods: The study was conducted on 4595 plasma samples from donors who donated in 14 different Blood Establishments in the Lazio Region, in the period June–November 2017. A total of 389 of these samples were collected in provinces not affected by the outbreak and were used as negative controls. All samples were tested for IgM detection by the use of an ELISA test, and positive samples were tested for confirmation through the use of a PRNT. Molecular tests were performed on sera that were found to be IgM-positive or borderline. Results: A total of 41 (0.89%) blood donors tested positive for IgM. None of these positive IgM ELISA results was confirmed either by PRNT or by molecular tests. Conclusions: Our study has shown no evidence of recent/ongoing CHIKV infection in blood donors of the affected area.